2020
DOI: 10.1016/j.ebiom.2019.102615
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells ameliorate β cell dysfunction of human type 2 diabetic islets by reversing β cell dedifferentiation

Abstract: A B S T R A C TBackground: A physiological hallmark of patients with type 2 diabetes mellitus (T2DM) is b cell dysfunction.Despite adequate treatment, it is an irreversible process that follows disease progression. Therefore, the development of novel therapies that restore b cell function is of utmost importance.Methods: This study aims to unveil the mechanistic action of mesenchymal stem cells (MSCs) by investigating its impact on isolated human T2DM islets ex vivo and in vivo.Findings: We propose that MSCs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 60 publications
2
43
0
Order By: Relevance
“…For decades, the authors of the present study, as well as others, have reported the clinical and preclinical applicability of MSCs in refractory and recurrent diseases, such as Crohn's disease, aplastic anemia, acute myocardial infarction, GVHD and even H5N1-infected pneumonia which cause acute lung injury and acute respiratory distress syndrome (ALI/ARDS), which are similar to the symptoms of SARS-CoV-2 infection (20,24,25,42,43,45). Very recently, Leng et al and Wang et al reported the clinical remission of a 65-year-old female critically ill patient with COVID-19 with hUC-MSC transplantation for 3 times as well, whereas the lung damage was relatively mild, which was confirmed by another studies (14,32). However, the safety and effectiveness assessment on elderly patients critically ill with COVID-19 with severe pneumonia-induced ARDS and MODS-associated multiple comorbidities remains largely unknown.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…For decades, the authors of the present study, as well as others, have reported the clinical and preclinical applicability of MSCs in refractory and recurrent diseases, such as Crohn's disease, aplastic anemia, acute myocardial infarction, GVHD and even H5N1-infected pneumonia which cause acute lung injury and acute respiratory distress syndrome (ALI/ARDS), which are similar to the symptoms of SARS-CoV-2 infection (20,24,25,42,43,45). Very recently, Leng et al and Wang et al reported the clinical remission of a 65-year-old female critically ill patient with COVID-19 with hUC-MSC transplantation for 3 times as well, whereas the lung damage was relatively mild, which was confirmed by another studies (14,32). However, the safety and effectiveness assessment on elderly patients critically ill with COVID-19 with severe pneumonia-induced ARDS and MODS-associated multiple comorbidities remains largely unknown.…”
Section: Discussionmentioning
confidence: 72%
“…In general,SARS-CoV-2 belongs to the genus and exhibits great phylogenetic similarity to the coronavirus from bats, which is distinguished from the 2003 SARS-CoV and the Middle East respiratory syndrome coronavirus (MERS-CoV) at the molecular level (7,8,32,(34)(35)(36)(37). Despite the early outbreak of COVID-19 in Wuhan of China, yet increasingly evidences were inclined to dismiss the possibility from the classification of SARS-CoV-2 (33,34,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA extraction and cDNA synthesis were performed by utilizing the RNeasy Mini Kit (QIAGEN) and PrimeScript RT reagent Kit with gDNA Eraser (Takara) as we described ( 23 ). qRT-PCR was performed with SYBR Premix ExTaq II (Takara) and LightCycler96 System (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Similar phenomenon was also observed in ASCs derived from subcutaneous adipose tissue compared with ND-ASCs ( 3 , 22 ). With regard to DM, MSCs have been recognized as a pivotal microenvironmental ingredient for the secretion of multiple cytokines and inflammatory factors (e.g., VEGF , IL-6 , TNF- α ) and the transdifferentiation into insulin-secreting β cells in the pancreas as well ( 7 , 17 , 23 ). Studies on experimental type 1 diabetic mouse model showed that T1DM mice-derived BM-MSCs exhibited indistinguishable characteristics including cytomorphology, immunosuppressive and migration capabilities as the control mice but with abnormally elevated expression of mediators such as MIP-1 α / β , MCP-1/5 , CCL-2 , CCL-3 and IL-6 , which facilitated recruitment and accumulation of inflammatory M1 macrophages and aggravated the occurrence of diabetic complications ( 2 , 6 , 17 , 22 ).…”
Section: Introductionmentioning
confidence: 99%